Why are they hard to treat? A preliminary survey to predict important factors causing persistent scabies among students of religion-affiliated boarding schools in Indonesia - Rahadi Rihatmadja; Eliza Miranda; Melani Marissa Wicaksono; Sandra Widaty (PAGEPress Publications, 2019)
Scabies is difficult to treat in some settings. By observation, it is highly prevalent among students of religion-affiliated boarding schools in Indonesia. Treatment often results in temporary relief. It is known that treatment alone will fail if personal hygiene and environment problems are not addressed. The aforementioned boarding schools have certain challenging characteristics, and several studies have found they might influence those problems. Our study aimed to specify and describe the characteristics to prepare future mass treatment in tackling with the problems. The study recruited and interviewed 105 students of a boarding school located in West Java region. The problems identified were sharing clothes/prayer attire among students, infrequent washing of clothes, availability of hot water, sharing beds, lack of bed sheet, and the presence of scabies among friends and siblings at home. A successful treatment plan must provide means to improve these habits.